Macrophage colony-stimulating factor and its role in the tumor microenvironment: novel therapeutic avenues and mechanistic insights - Yi, Li; Gai, Yihan; Chen, Zhuo; Tian, Kecan; Liu, Pengfei; Liang, Hongrui; Xu, Xinyu; Peng, Qiuyi; Luo, Xiaoqing (Frontiers in Oncology, 2024)
The tumor microenvironment is a complex ecosystem where various cellular and molecular interactions shape the course of cancer progression. Macrophage colony-stimulating factor (M-CSF) plays a pivotal role in this context. This study delves into the biological properties and functions of M-CSF in regulating tumor-associated macrophages (TAMs) and its role in modulating host immune responses. Through the specific binding to its receptor colony-stimulating factor 1 receptor (CSF-1R), M-CSF orchestrates a cascade of downstream signaling pathways to modulate macrophage activation, polarization, and proliferation. Furthermore, M-CSF extends its influence to other immune cell populations, including dendritic cells. Notably, the heightened expression of M-CSF within the tumor microenvironment is often associated with dismal patient prognoses.Therefore, a comprehensive investigation into the roles of M-CSF in tumor growth advances our comprehension of tumor development mechanisms and unveils promising novel strategies and approaches for cancer treatment.